1979
DOI: 10.1136/vr.104.21.480
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical observations on beagle dog semen

Abstract: Semen samples were collected at weekly intervals for six weeks from eight sexually mature beagles previously shown to produce normal ejaculates. Seminal plasma and sperm fractions were separated by centrifugation and the sodium, potassium, alanine and aspartate aminotransferases, acid and alkaline phosphatase concentrations in the two fractions determined. Regression analysis of the mean weekly values obtained from physical and biochemical examination of the ejaculates showed that sodium ion concentration was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

1979
1979
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Comparison of our data with the previously published results is complicated because several authors analysed seminal plasma of mixed ejaculate fractions (De Souza, Martins, & Lopes, ) or did not mention which fractions the seminal plasma was obtained from (James, Heywood, & Street, ; Schäfer‐Somi, Blickensdörfer, & Schwendenwein, ). Additionally, preparation of seminal plasma differed considerably between studies in term of centrifugation speed (range: 700 g–4000 g) and duration (range: 15–30 min).…”
Section: Discussionmentioning
confidence: 66%
“…Comparison of our data with the previously published results is complicated because several authors analysed seminal plasma of mixed ejaculate fractions (De Souza, Martins, & Lopes, ) or did not mention which fractions the seminal plasma was obtained from (James, Heywood, & Street, ; Schäfer‐Somi, Blickensdörfer, & Schwendenwein, ). Additionally, preparation of seminal plasma differed considerably between studies in term of centrifugation speed (range: 700 g–4000 g) and duration (range: 15–30 min).…”
Section: Discussionmentioning
confidence: 66%
“…Also in line with these findings, Johnston (1991) reported that normospermic dogs have concentrations of AP in seminal plasma that ranged from 5000 to 40 000 U/L. ; whereas James et al (1979) reported AP concentrations that ranged from 5500 to 14 000 U/L. AP concentrations in either semen fractions or in seminal plasma (after centrifugation) are a useful test to differentiate between the collection of an incomplete ejaculate (little or no second fraction collected), obstructive azoospermia (obstruction of the vasa deferentia or epididymides) and azoospermia as a result of gonadal dysfunction (testicular hypoplasia and degeneration) or to unilateral or bilateral aplasia of the epididymides (Johnston 1991, Olson et al 1992, Meyers‐Wallen 1995).…”
Section: Discussionmentioning
confidence: 54%
“…The normal semen quality values in adult Beagle dogs are reported to be: total semen volume, 7-12 ml; total number of sperm, 300-500 × 10 6 ; sperm motility, 80-90%; and percentages of abnormal sperm and immature sperm, 5-12% and 1-2%, respectively [3,17,20,22,38,40]. Normal values of pH, osmotic pressure, and Na + ·K + concentrations in the second semen fraction of dogs are reported to be of 6.7-6.8, 280-300 mOs/kg, 192 m M/l and 12.4 m M/l, respectively [2,6,22,43].…”
Section: Discussionmentioning
confidence: 99%
“…The body weight of the Beagle dogs and the mongrel dogs ranged from 12 kg to 15 kg, and the Shetland sheep dog weighed 20 kg. All of the dogs were diagnosed as having both asthenozoospermia and teratozoospermia, based on a comparison of their semen quality (Table 1) and with other reports on normal semen quality in dogs [17,20,38]. The dogs were housed in pens with runs under natural lighting, and water was available ad libitum.…”
mentioning
confidence: 99%